Combined In vitro Effects of TiO2 Nanoparticles and Dimethyl Sulfoxide (DMSO) on HepG2 Hepatocytes - Andreea R Lupu; Lidia Cremer; Traian Popescu (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2015)
Introduction: Professional workers that manufacture or use titanium dioxide (TiO2)-based paints are exposed to potentially toxic TiO2 nanomaterials as well as to different paint solvents such as dimethyl sulfoxide (DMSO). In this context, we evaluate the combined cytotoxic effects of TiO2 nanoparticles and DMSO on HepG2 human hepatocytes. Methods: Three types of TiO2 nanoparticles were used: commercial Degussa P25 and two samples synthesized by a hydrothermal procedure - undoped and Fe3+-doped TiO2. The effects of TiO2 nanoparticles on HepG2 cells exposed to DMSO before, after or together with the TiO2 treatment were investigated by viability and intracellular reactive oxygen species (ROS) determinations, performed using the MTT and DCFH-DA(2',7'-dichlorﬂuorescein-diacetate) methods respectively.  Results: Results indicated that DMSO made HepG2 cells more susceptible to toxic effects induced by nanosized TiO2. In the absence of DMSO, none of the tested nanoparticles exhibited significant cytotoxic effects. Viability increases were detected after 48 hours of treatment and attributed to possible redox-sensitive proliferation mechanism striggered by the low and moderate amounts of produced ROS. The combined action of TiO2 and DMSO led to a general viability decrease tendency. Significant effects (viability reductions and ROS generation) were observed in the case of cells first treated with Degussa P25 TiO2 and afterwards exposed to DMSO. The hydrothermal materials exhibited reduced in vitro reactivity on HepG2hepatocytes.  Conclusion: The study reveals the enhancement of nanosized TiO2 toxicity induced by DMSO exposure, its findings having potential to help in the evaluation of professional health risks associated to the combined action of TiO2 nanomaterials and paint solvents.